Breast cancer survival rates in Sarawak, Malaysia: a central referral centre study - Melissa Lim, Siaw Han; Shirley Tan, Siang Ning; Izzati, Wan Maharuddin; Sharifah Ashrina, Wan Ali; Tiong, Xun Ting; Chew, Keng Sheng; Adam Malik, Ismail; Yolanda, Augustin; Voon, Pei Jye (Springer Nature Limited, 2026)
Background Breast cancer remains the most common malignancy in Malaysia, with a wide range of survival rates across regions. Sarawak, the largest state in Malaysia faces unique geographic and socioeconomic challenges, often delaying diagnosis and treatment. This study aimed to determine the survival rates and predictors of breast cancer outcomes at the state’s sole public referral centre for cancer.